Revitalisasi Pasar Tradisional Dalam Perspektif Good Governance(Studi Di Pasar Tumpang Kabupaten Malang) - Ella Alfianita (Jurnal Administrasi Publik, 2015)
Abstract: Revitalization of Traditional Market Based On Good Governance Perspective (A Study at Tumpang Market in Kabupaten Malang). Revitalization policy of traditional markets is very important to be implemented, as we know it hs been known that there is an unhealthy competition between the traditional and the modern market. This policy is succesfully implemented, is the Tumpang Market in Kabupaten Malang. This research aims to identyfy, analyze, and describe patterns of cooperation among actors that involved in the revitalization of traditional markets in Tumpang Market based on perspective good governance and efforts taken in the revitalization of the market. This research using qualitative descriptive research methods. Agreements made could be goingÂ  well which can be measured from the four principles of good governance, such as accountability, partisipation, predictibility (rule of law) and transparancy. Efforts that have been taken consisting of the precisely physical aspects (development and improvement of market structure) and non-physical aspects (fostering and empowermentof human resource). Keywords: revitalization, Traditional Market, Good Governance Perspective Abstrak: Revitalisasi Pasar Tradisional dalam Perspektif Good Governance (Studi di Pasar Tumpang Kabupaten Malang). Kebijakan revitalisasi pasar tradisional penting diimplementasikan, karena seperti yang telah diketahui bahwa terjadi persaingan yang tidak sehat antara pasar tradisional dan pasar modern. Kebijakan ini berhasil diimplementasikan yang salah satunya pada Pasar Tumpang Kabupaten Malang. Penelitian ini bertujuan untuk mengetahui, menganalisis dan menggambarkan pola kerjasama antar aktor dalam revitalisasi pasar tradisional di Pasar Tumpang Kabupaten Malang dalam perspektif good governance dan upaya apasaja yang diambil dalam revitalisasi pasar tradisional di Pasar Tumpang Kabupaten Malang. Penelitian ini menggunakan metode penelitian deskriptif kualitatif. Kerjasama yang telah dilakukan dapat dikatakan berjalan dengan baik yang dapat diukur dari empat prinsip good governance, antara lain accountability, partisipation, predictibility (rule of law), dan transparancy. Upaya yang telah diambil terdiri dari aspek fisik (pembangunan dan perbaikan fasilitas pasar) dan aspek nonfisik (pembinaan dan pemberdayaan sumber daya manusia). Â  Kata Kunci: revitalisasi, Pasar Tradisional, Perspektif Good Governance